Respiratory morbidity in very preterm and very low birth weight infants: the first 2 years of life - Mariana Ferreira; Manuel Ferreira de Magalhães; Gustavo Rocha; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2014)
Respiratory morbidity in the first two years of life, including recurrent symptoms and frequent hospitalizations, is a common problem in very preterm and very low birth weight (VLBW) infants. We conducted a retrospective cohort study aiming to describe the respiratory morbidity at 2 years of corrected age for very preterm and VLBW infants and to identify potential risk factors for its development in a Portuguese based population born in a tertiary referral center between 2009 and 2011. Data were collected from patient's clinical files and using a standardized questionnaire-based clinical interview for parents. A total 59 children were included. Thirteen (22.0%) had recurrent respiratory symptoms and 12 (20.3%) were using chronic respiratory medication. Health care utilization for respiratory causes was frequent (57.6%), particularly emergency department attendance (50.8%). Twenty seven (45.8%) had additional outpatient visits for respiratory causes and hospital admission was necessary for 8 (13.6%) patients. Factors associated with increased recurrent respiratory symptoms included maternal hypertensive disorders during pregnancy, umbilical artery flow disturbances, being small for gestational age, bronchopulmonary dysplasia, retinopathy of prematurity, intraventricular hemorrhage and a weight percentile below 3 at 6, 12 and 24 months of corrected age. Premature rupture of membranes was negatively associated with respiratory morbidity. Respiratory morbidity at 2 years of age is a common problem in very preterm and VLBW children from our population. Several perinatal and developmental risk factors were identified for respiratory morbidity. Further studies are needed to clarify the importance of these factors, as they can lead to changes in healthcare guidelines.